Removal of arsenic from simulated groundwater using calcined laterite as the adsorbent - Nguyen, Phuong Thi Ngoc (Animo Repository, 2011)
Arsenic in groundwater poses a health hazard for rural areas all over the world, especially in developing countries. This paper reports the findings of a batch study performed to identify the best possible method for the preparation of an adsorbent for arsenic removal from groundwater. The study also includes the effects of column parameters on the removal of arsenic. The results show that laterite, because of its high iron content, has promising applications in arsenic treatment. Batch experiments for the adsorption of arsenic on laterite calcined at different temperatures were performed to identify the appropriate conditions for the preparation of the adsorbent. Laterite calcined at 400°C could remove 99.42% of arsenic from simulated groundwater, and thus, the treated water met the WHO standard for drinking water. Characterization of the calcined laterite by XRF, EDX, XRD, BET, and SEM analyses confirmed the successful adsorption of arsenic by laterite. The adsorption equilibrium was determined by varying the initial arsenic concentration from 0.361 to 5.073 mg/L in the batch experiments. The Langmuir and Freundlich isotherm models supported the experimental data. The effect of various column operation parameters such as space velocity, inlet arsenic concentration, and adsorbent bed height on the column performance was investigated. The BDST model was also useful in predicting the column parameter constants. In summary, it was demonstrated that calcined laterite is a low-cost adsorbent that is effective and suitable for the arsenic treatment of groundwater. © 2011 The Society of Chemical Engineers, Japan.